MENYIAPKAN SUMBER DAYA MANUSIA DALAM MEWUJUDKAN GENERASI ISLAM MODERN: Studi Peran Guru Kelas pada pembelajaran matematika di SDN Bangah - Huda, Nuril; Setiawan, Windi (Universitas Nahdlatul Ulama Pasuruan, 2023)
The main focus in the global arena is the issue of competition, one of the competitions in it is the world of education. It is not only the responsibility of religious education that plays a role in printing and preparing future generations called the modern Islamic generation, but all educators have a moral responsibility to prepare a good generation, and have high integrity in religion. The ability to manage change, the ability to act, the ability to process all information globally, analytical skills, interpersonal skills, interpersonal skills are the parts that must be prepared to play a role as a teacher, including a teacher in the field of mathematics studies. Some of these competencies must be taught, delivered to students during the learning process. In this research activity, the focus is on the role of educators, especially mathematics education teachers, as an effort to prepare a generation that will enter the community as part of a society that has the power of religion, namely Islam. More than that, it is functioned to increase human resources (HR) who are able to carry out the principles of Islamic teachings in the midst of a rapidly developing society in technology. A behavior that is built in the context of learning mathematics is honest, consistent, balanced, careful thinking, critical, always curious and thorough